Kinematic models of basement/cover interaction: Insights from the Malargüe fold and thrust belt, Mendoza, Argentina - Giambiagi, Laura Beatriz (2009)
We investigate through natural examples from the Malargüe fold and thrust belt the manner in which the basement structures interact with the cover in a thick-skinned fold and thrust belt. Our work suggests that there is a broad spectrum of basement-cover interaction mechanisms with two end-members: coupled and uncoupled interactions. The kind of bonding between basement and cover is related to the propagation to slip ratio (p/s), because high values of this ratio indicate rapid forward propagation of shortening into the cover, while low values favour welding between basement and cover structures. We analyse the factors controlling the kinematics of basement-cover deformation, and find that not only the strength of the cover, its thickness, and its mechanical anisotropy control the p/s and basement-cover bonding, but also the strain rate, the thickness of synorogenic strata, and the presence of pre-existing faults.